Efeito na saúde periodontal do momento de intervenção restauradora em dentes posteriores após cirúrgica periodontal - estudo clínico no ambiente do SUS - Oliveira, Rita Catarina (2024)
This study aimed to evaluate the impact of the timing of restorative intervention on periodontal health in posterior teeth following periodontal surgery. The objective was to examine changes in periodontal tissue levels after clinical crown lengthening. Twenty two systemically healthy adult patients requiring crown lengthening procedures to reestablish the biological width and rehabilitate with composite resin were evaluated. Clinical parameters were recorded over the evaluation period using a standardized stent. Bone reduction was performed based on the minimal amount of dental structure necessary for restorative purposes. The results indicated a significant difference in gingival margin measurements relative to the restoration margin (-1.12 ± 0.21 mm) (p = 0.0003), with a coronal tissue rebound observed when comparing the two groups at the 60-day mark. This finding emphasizes the importance of maintaining biological width. The study highlights the critical relationship between periodontics and restorative procedures in achieving optimal esthetic outcomes and long-term periodontal health. These insights are valuable for improving treatment strategies and clinical practices, contributing to the stability of soft tissues and the success of restorative procedures.